Determination of root length reduction (EC50) by a glyphosate formulation using lettuce and wheat as biological indicator species - Lallana, María del C.; Lallana, Víctor H.; Billard, Cristina E.; Foti, María Natalia; Elizalde, José H. I. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The objective of this work was to determine a glyphosate formulation effects on the root length reduction (average effective concentration: EC50) using germination bioassays with lettuce and wheat seeds. For lettuce nine decreasing doses/treatments between 1,215 and 0.01215 g a.i.ha-1 (formulated as: N phosphonometyl glycine ammonium salt 40.5 [g e.a. glyphosate 36.9% p/v]) and for wheat five decreasing doses (12.15 and 1.215 g a.i.ha‑1) and their respective negative controls (distilled water) were tested. Bioassays were carried out in Petri boxes with wet filter paper with 3 ml of corresponding solution. Twenty seeds were sowed per box, treatments being distributed in blocks at random with 4 repetitions in germination chamber under alternating light and dark condition at 20°C. All seed average root length and repetition were estimated with a digital caliper. The average germination percentage of treatments and the germination index was also determined. EC50 or doses reducing 50% their radical growth for lettuce and wheat were 6.682 and 9.416 g a.i.ha-1. Plant materials tested resulted sensitive to the different glyphosate doses and they can be used as biological indicators of the specific toxicity.